1997
DOI: 10.1159/000106669
|View full text |Cite
|
Sign up to set email alerts
|

The Use of SPECT in a Multidisciplinary Memory Clinic

Abstract: We tested the interobserver reliability of visual rating of HMPAO-SPECT imaging in 271 outpatients referred to a memory clinic, and followed over 1 year. The clinical diagnoses were Alzheimer''s disease (n = 156), frontotemporal dementia (n = 47), vascular dementia (n = 21), senile dementia of Lewy body type (n = 12), anxiety/depressive disorders (n = 14) and miscellaneous memory disorders (n = 21). The interobserver agreement was good (k = 0.68). However, the heterogeneity of the patterns – independent from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 20 publications
(29 reference statements)
4
14
0
1
Order By: Relevance
“…The clinical diagnosis may be strongly supported by brain imaging such as regional cerebral blood flow measurement with the xenon inhalation technique [33,34], single-photon emission computerized tomography [35,36] and positron emission tomography. Most often, however, these patients are investigated with CT and MRI [37][38][39] because of the severe deterioration of personality and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical diagnosis may be strongly supported by brain imaging such as regional cerebral blood flow measurement with the xenon inhalation technique [33,34], single-photon emission computerized tomography [35,36] and positron emission tomography. Most often, however, these patients are investigated with CT and MRI [37][38][39] because of the severe deterioration of personality and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This frontal hypoperfusion predicted the frontal pathology that characterizes FTD. Others confirmed these observations [17][18][19][20][21][22][23], and quantitative studies with positron emission tomography (PET) showed that patients with Pick's disease had diminished frontal lobe glucose uptake suggesting altered neuronal metabolism in the anterior brain regions [24][25][26][27][28]. Yet, despite these elegant clinical and imaging studies which should have allowed accurate diagnosis of FTD, the misdiagnosis rate for this condition has remained high [14].…”
Section: Historical Reviewmentioning
confidence: 99%
“…Qualitative visual assessment of PET scans can be reliable (intra-observer = 0.56; interobserver = 0.51) [7], as can be SPECT [8,9], particularly if well defined classification criteria are used [10,11].…”
Section: Image Analysis Methodsmentioning
confidence: 99%